Effect of Distal Ulna Osteochondroma Excision and Distal Ulnar Tether Release on Forearm Deformity in Preadolescent Patients With Multiple Hereditary Exostosis. Issue 3 (March 2020) - Belyea, Christopher; Pulos, Nicholas; Ezaki, Marybeth; Wall, Lindley; Mills, Janith; Beckwith, Terri; Oishi, Scott N.
Abstract : Background: Multiple hereditary exostosis is a benign condition that can lead to significant forearm deformity secondary to physeal disturbances. As the child grows, the deformity can worsen as relative shortening of the ulna causes tethering, which may lead to increased radial articular angle, carpal slippage, and radial bowing, over time this tethering can also result in radial head subluxation or frank dislocation. Worsening of forearm deformities often require corrective reconstructive osteotomies to improve anatomic alignment and function. The purpose of this study is to evaluate the effectiveness of osteochondroma excision and distal ulnar tether release on clinical function, radiographic anatomic forearm alignment, and need for future corrective osteotomies. Methods: The authors reviewed a retrospective cohort of preadolescent patients who underwent distal ulna osteochondroma resection and ulnar tethering release (triangular fibrocartilage complex). Patients were invited back and prospectively evaluated for postoperative range of motion, pain scores, self-reported and parent-reported Disabilities of the Arm, Shoulder, and Hand (DASH) and Pediatric Outcomes Data Collection Instrument (PODCI) scores. In addition, preoperative and final postsurgical follow-up forearm x-rays were reviewed. Results: A total of 6 patients and 7 forearms were included in our study with an average age of 7.9 years at time of surgery. The average final follow-up was 7.4 years. With respect to range of motion, only passive radial deviation demonstrated improvement −20 to 14 degrees ( P =0.01). Although there was not statistically significant change in radial articular angle, this study did find an improvement in carpal slip 75.7% to 53.8% ( P =0.03). At final follow-up DASH score was 5.71 (σ=5.35), PODCI Global Function score was 95.2 (σ=5.81), and PODCI-Happiness score 98 (σ=2.74). Visual analogue scale appearance and visual analogue scale pain assessment were 1.67 (σ=1.21) and 1.00 (σ=1.26), respectively, at final follow-up. No patient in the cohort developed a radial head dislocation. Only one of 7 forearms required a corrective osteotomy within the study's follow-up time period. Conclusions: Surgical excision of forearm osteochondromas with ulnar tether release in the preadolescent patients improves carpal slip, may help to prevent subsequent surgical reconstruction and provides satisfactory clinical results at an average 7-year follow-up. Level of Evidence: Level III—therapeutic study.